Optimization of drilling process parameters for self-lubricants reinforced aluminium metal matrix composites. (2022) - Saravanakumar, A.; Sreenivas, P.; Vijaya kumar, S.; Pradeep kumar, U.; Rajeshkumar, L.
Abstract: Aluminium matrix composites (AMCs) find a wide spectrum of application in various fields of engineering and technology. Owing to the below par inherent characteristics of unreinforced AMCs, reinforcements are used to improve the characteristics of AMCs. Reinforcing the self-lubricating graphite (Gr) and molybdenum disulphide (MoS2 ) in aluminium matrix was found to improve the machinability and surface finish of the composites which in turn enhances the application prospects. In the current investigation, aluminium alloy 2219 (AA2219) was reinforced with Gr and MoS2 and the composites were fabricated by conventional casting technique. Drilling behavior of the composites were investigated by conducting drilling experiments in CNC machining center and surface roughness of the holes were measured. Experiments were designed by full factorial method. Results of the experiments portrayed that the composites with Gr as reinforcement exhibited better drilling behavior when compared with MoS2 reinforced AA2219 composites.